Pesantren, Madrasa and the Future of Islamic Education in Indonesia - Ronald Lukens-Bull (Kawalu: Journal of Local Culture, 2019)
This article delineates the development of pesantren and madrasa as a very significant part of Islamic education in Indonesia. In doing so, I explore three points related to the development. Firstly, there is an ancient tradition of accommodation in Indonesian Islamic education world. This is seen in the foundation myths that traditional pesantren use to understand their role in society. Secondly, there is a desire to modernize and to meet the modern needs of both students and society while maintaining firm roots in traditional Islamic education. It must be an on-going ‘evolutionary’ process. Thirdly, pesantren people have rejected the sharia state, the khilafa, the use of violence, and narrow understandings of what the nation should be. They have worked hard to distance themselves from others that seek to cloak themselves in their legitimacy. Therefore, I would argue that the pesantren and other forms of Islamic education will contribute to the future of Indonesia as a plural, peaceful and democratic society.